Radial velocity measurements and orbit determination of eight single‐lined spectroscopic binary systems1. Issue 6 (18th July 2017) - Bischoff, R.; Mugrauer, M.; Zehe, T.; Wöckel, D.; Pannicke, A.; Lux, O.; Wagner, D.; Heyne, T.; Adam, C.; Neuhäuser, R.
Abstract : Since early 2015, a new radial velocity monitoring campaign is going on at the University Observatory Jena. The aim of this project is to obtain current radial velocity measurements of selected single‐lined spectroscopic binary systems as well as to redetermine and/or constrain their orbital solutions. In this paper, we characterize the properties of the target sample of the project, describe the spectroscopic observations, data reduction, and analysis, and present the first results of the project, taken with the fiber‐linked astronomical spectrograph FLECHAS. We present 391 radial velocity measurements of eight spectroscopic binaries, which were taken within an epoch difference of 1.6 years. These radial velocities were used to determine the spectroscopic orbital elements of the observed binary systems, which exhibit orbital periods in the range between nearly one up to several dozens of days. We could constrain the orbital solutions of seven of these binary systems, and redetermine the orbital solution of φ Dra, whose orbit exhibits >4 times longer orbital period and is more eccentric than given in the 9th Catalogue of Spectroscopic Binary Orbits.